Associations between Attention-Deficit/Hyperactivity Disorder and Ocular Abnormalities in Children: A Population-based Study. (3rd May 2020) - Ho, Jau-Der; Sheu, Jau-Jiuan; Kao, Yi-Wei; Shia, Ben-Chang; Lin, Herng-Ching
ABSTRACT: Purpose : Attention-deficit/hyperactivity disorder (ADHD) was reported to be associated with disturbances in the prefrontal circuitry and seems to be associated with dysfunctions of eye motility. This study aimed to explore associations between ADHD and ocular abnormalities, including amblyopia, hypermetropia, astigmatism, and heterotropia, using a large, nationwide population-based dataset in Taiwan. Methods : We retrieved our sample for this cross-sectional study from the Taiwan National Health Insurance Research Database. In total, 116, 308 children with ADHD were selected as the study group and 116, 308 randomly selected children without ADHD as the comparison group. We used conditional logistic regression analyses to examine the odds ratios (ORs) of amblyopia, hypermetropia, astigmatism, and heterotropia between children with and those without ADHD. Results : We found that children with ADHD had significantly higher prevalences of amblyopia (1.6% vs. 0.9%, p < .001), hypermetropia (2.4% vs. 1.3%, p < .001), astigmatism (0.2% vs. 0.1%, p < .001), and heterotropia (1.1% vs. 0.5%, p < .001) than children without ADHD. The ORs of amblyopia, hypermetropia, astigmatism and heterotropia for children with ADHD were 1.89 (95% confidence interval (CI) = 1.76 2.05), 1.82 (95% CI = 1.68 1.92), 1.73 (95% CI = 1.34 2.16), and 2.01 (95% CI = 1.82 2.21) compared to children without ADHD. Conclusions : The findings suggest that ADHD is associated with ocular abnormalities, including amblyopia, hypermetropia, astigmatism, and heterotropia.